Characterization of glycerophospholipid molecular species in muscles from three species of cephalopods by direct infusion-tandem mass spectrometry. (January 2020) - Shen, Yan; Xie, Hong-Kai; Liu, Zhong-Yuan; Lu, Ting; Yu, Zhuo-Liang; Zhang, Li-Hua; Zhou, Da-Yong; Wang, Tong
Highlights: Total lipids were recovered from muscle of cephalopod using methyl tert-butyl ether method. Lipid class compositions were determined using thin layer chromatography-flame ionization detection. Phospholipid class compositions were determined using 31 P nuclear magnetic resonance. Fatty acyl composition was analyzed using gas chromatography-mass spectrometry. Glycerophospholipids were characterized using direct infusion-tandem mass spectrometry. Abstract: More than 200 molecular species of glycerophospholipids (GP) including glycerophosphocholine (GPC), glycerophosphoethanolamine (GPE), glycerophosphoserine (GPS), lysoglycerophosphocholine (LGPC), lysoglycerophosphoethanolamine (LGPE) and lysoglycerophosphoserine (LGPS), as well as 18 kinds of sphingomyelin (SM) were characterized by using a direct infusion-tandem mass (MS/MS) spectrometry method for lipids from the muscles of cephalopods Sepiella maindroni, Octopus ocellatus and Loligo chinensis for the first time. The majority of the GP molecular species contained long-chain omega-3 polyunsaturated fatty acids (n-3 LC-PUFA), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Therefore, cephalopods can be a good possible source of dietary GP carrying n-3 LC-PUFA. The total lipids were composed of phospholipid (PL, 72.29–83.32 wt% of total lipids), cholesterol (12.70–23.60 wt% of total lipids), triacylglycerol (1.86–2.93 wt% of total lipids), diacylglycerol (0.15–1.09 wt% of total lipids), monoacylglycerol (0.06-0.18 wt% of total lipids) and free fatty acid (0.72–1.86 wt% of total lipids). For PL, phosphatidylcholine (44.47–62.30 mol%), phosphatidylethanolamine (22.57–39.08 mol%), phosphatidylserine (6.15–10.18 mol%), phosphatidylglycerol (0.68–3.11 mol%), phosphatidylinositol (2.41–7.15 mol%) and lysophosphatidylcholine (1.84–5.24 mol%) were detected. Furthermore, the total lipids from the muscles of cephalopods Sepiella maindroni, Octopus ocellatus and Loligo chinensis contained 41.80–50.02 mol% of saturated fatty acids, 11.53–21.54 mol% of monounsaturated fatty acids and 36.67–40.82 mol% of PUFA, whilst DHA (15.25–26.71 mol%) and EPA (6.29–16.57 mol%) were found to account for the majority of the PUFA. With these data presented, cephalopod muscle can be considered as a healthy food for humans.